2018
DOI: 10.1007/s42113-018-0004-6
|View full text |Cite
|
Sign up to set email alerts
|

Cueing Effects in the Attentional Network Test: a Spotlight Diffusion Model Analysis

Abstract: The attentional network test (ANT) uses flanker stimuli with different cue conditions to quantify differences in attentional processing. However, it is unclear precisely how the alerting and orienting cues in the task affect different decision processes. The present study leveraged computational modeling to identify the relationship between attentional cues and decision components. ANT data from a large sample of 156 participants were analyzed using the spotlight diffusion model, which quantifies decision comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…To confirm the origin of the observed flanker effects, data (RT & accuracy) were submitted to an additional Shrinking Spotlight (SSP) Diffusion Model analysis (White et al, 2011;White & Curl, 2018). The SSP is an extension of the Drift Diffusion Model (DDM) of decision-making and was developed to elucidate the cognitive operations that underpin performance during flanker tasks (White et al, 2011).…”
Section: Shrinking Spotlight Diffusion Model Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…To confirm the origin of the observed flanker effects, data (RT & accuracy) were submitted to an additional Shrinking Spotlight (SSP) Diffusion Model analysis (White et al, 2011;White & Curl, 2018). The SSP is an extension of the Drift Diffusion Model (DDM) of decision-making and was developed to elucidate the cognitive operations that underpin performance during flanker tasks (White et al, 2011).…”
Section: Shrinking Spotlight Diffusion Model Analysismentioning
confidence: 99%
“…To estimate the parameters of the SSP, data (i.e., RT quantiles and accuracy) were submitted to the fitting procedure adopted by White and Curl (2018). Apart from the spotlight width (sd a ), all parameters (a, p, Ter, s d ) varied as a function of Target Association (i.e., self vs. friend) and were fitted separately for each participant (see Supplemental Materials for a listing of the parameter estimates).…”
Section: Shrinking Spotlight Diffusion Model Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The system has three functionally and anatomically separate networks with specific and separable forms of attention, namely alarm, orientation, and executive attention. Executive attention networks are also known as collision networks [25].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…They showed that meditators adapted their level of caution more to the task conditions than controls, although the effect of meditation practice was not very strong. A critical note here is that the drift diffusion model they used was not adapted specifically to the Attention Network Task [14], which may have resulted in inaccuracies in the parameter estimates.…”
Section: Main Bodymentioning
confidence: 99%